Pavement temperature mitigation by the means of geothermally and solar heated air - Chiarelli, Andrea; Dawson, Andrew; Garcia, Alvaro (Elsevier, 2017)
In this article, a novel method to mitigate pavement temperatures by the means of air convection is presented. The technique introduced here is based on a new type of experimental setup called a ground source heat simulator, which is able to feed air at a controlled temperature to a set of pipes embedded under a test pavement surface. The air at the chosen temperature can flow through the designed system by natural convection. The air heated by the simulated geothermal source can mitigate the pavement temperature in winter and summer conditions in order to avoid freezing and overheating of paving surfaces in an urban environment. In particular, during winter the geothermal air warms up the pavement, while during summer the pavement is cooled down. Laboratory tests of the ground source heat simulator allowed the collection of a high amount of data, which is here analysed statistically and computationally. This article shows that the use of geothermal energy to preheat the inlet air in pavements where an array of pipes is installed can provide a measurable contribution for the mitigation of pavement temperatures in both winter and summer conditions. Furthermore, the experimental data gathered successfully proved the effectiveness of computational simulations for the study of buoyancy powered air flow through channels buried under pavements and increased the understanding of the physical phenomena happening in the system under analysis. Finally, preliminary testing in the environment showed that the concept is effective and works as expected.